Effectiveness of topical and ablative therapies in treatment of anogenital warts: a systematic review and network meta-analysis. Issue 10 (31st October 2019) - Barton, Samantha; Wakefield, Victoria; O'Mahony, Colm; Edwards, Steven
Abstract : Objective: To generate estimates of comparative clinical effectiveness for interventions used in the treatment of anogenital warts (AGWs) through the systematic review, appraisal and synthesis of data from randomised controlled trials (RCTs). Design: Systematic review and network meta-analysis of RCTs. Search strategies were developed for MEDLINE, Embase, the Cochrane Library and the Web of Science. For electronic databases, searches were run from inception to March 2018. The systematic review was carried out following the general principles recommended in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement. Participants: People aged ≥16 years with clinically diagnosed AGWs (irrespective of biopsy confirmation). Interventions: Topical and ablative treatments recommended by the British Association for Sexual Health and HIV for the treatment of AGWs, either as monotherapy or in combination versus each other. Outcome measures: Complete clearance of AGWs at the end of treatment and at other scheduled visits, and rate of recurrence. Results: Thirty-seven RCTs met inclusion criteria. Twenty studies were assessed as being at unclear risk of bias, with the remaining studies categorised as high risk of bias. Network meta-analysis indicates that, of the treatment options compared, carbon dioxide laser therapy is the most effective treatment for achieving complete clearance of AGWs at the end of treatment. Of patient-applied topical treatments, podophyllotoxin 0.5% solution was found to be the most effective at achieving complete clearance, and was associated with a statistically significant difference compared with imiquimod 5% cream and polyphenon E 10% ointment (p<0.05). Few data were available on recurrence of AGWs after complete clearance. Of the interventions evaluated, surgical excision was the most effective at minimising risk of recurrence. Conclusion: Of the studies assessed, as a collective, the quality of the evidence is low. Few studies are available that evaluate treatment options versus each other. Trial registration number: CRD42013005457